Attorney and President Relationship in Independent Aspects of the Indonesian State System after Reform - Imawan Sugiharto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The Attorney General's Office has a central position and a strategic role in a constitutional state because the Attorney General's Office acts as a filter between the investigation process and the examination process at trial; The position in the sense of the position and function of the Prosecutor's Office is very vulnerable to the state administration system or the style of government adopted. After the reform, the Prosecutor's Office underwent several changes in the system used. The method used by the researcher in this research is normative juridical with a descriptive analysis approach in the perspective of comparative historical politics. The discussion in this study uses a comparative political approach. This research provides an overview of the ideal concept of the Attorney General's Office in the state administration system of the Republic of Indonesia by placing the Prosecutor's Office with an independent nature that supports its duties and authorities in the field of prosecution both in theory and in fact. This must be regulated clearly and firmly in the constitution.